A educação financeira nos anos finais da educação básica: uma análise na perspectiva do livro didático - Trindade, Lilian Brazile (2017)
This research has as object of study the Financial Education and the objective of analyzing the approach of this theme in the final years of Basic Education, through the guidelines of the official documents, listing the mathematical and didactic organization presented in the Textbook. The choice of the collection of books analyzed, approved by the National Textbook Program in force, which has three volumes, one for each year of High School is presented in the chapter relating to theoretical methodological procedures. The analysis was subdivided into four stages, in which the first and the second are related to the quantification and analysis of the criteria established based on Federal Decree 7.397, created on 2010, which contemplate guiding subjects pertinent to Financial Education, the third stage presents the analysis of the mathematical organization through the Didactic Anthropological Theory and, finally, the analysis of the Didactic Organization of the collection, in the light of the Hypothetical Three-Dimensional Axis. It was observed the absence of the content approach regarding Financial Education in the National Curricular Parameters of High School, and that the exercises analyzed follow a line of technical procedures, in which the student is restricted to the resolutions through substitutions and applications of formulas, in a mechanical way, without any kind of reflection or criticism regarding decision making related to situations of their reality and also in adulthood